THE ENHANCING OF SPEAKING SKILL THROUGH THE APPLICATION OF COMMUNICATIVE LANGUAGE TEACHING (CLT) METHODE AT X RESTAURANT CLASS OF STATE VOCATIONAL HIGH SCHOOL PRAYA TENGAH (JURNAL MAHASANTRI, 2021)
English is an International language that widely used in Indonesia begining from Play Group to the University. Learning English is a must for the students in all of the schools, especially in State Vocational High School Praya Tengah. Being one of the most important subjects that need to be comprehended and mastered by its user. The main problem of this research is the Speaking Skill of X Restaurant students have not maximized. Therefore, it would be needed to use a teaching learning methode to enhance their skill in Speaking English. Communicative Language Teaching (CLT) is one of the methodes used in teaching learning process. Using this methode, hopefully the students’ English achievement especially in Speaking Basic Competency 5th which is Describing Events will be enhanced. The main objective of this research is to improve the teaching learning English in Speaking skill especially Describing Events that can be easier to be comprehended by the students through Communicative Language Teaching (CLT) methode. The action Hypotheses made by the researcher is “Communicative Language Teaching (CLT) methode will enhance the Students’ Speaking Skill in Learning English”. This research used Classroom Action Research that has four stages: 1) Plan, 2) Action, 3) Observation, and 4) Reflection. These four stages are organized in two cycles. The sources of data are the Speaking achievement of X Restaurant students and photograph. The data of the research are the students’ achievement, and the students’ process achievement, recorded of oral test, and observation. Based on the analysis result, it was found that the average of the students’process achievement in the first cycle is 63.71, and in the second cycle is 65.62. The average of the students’achievement in the first cycle is 87.50, and in the second cycle is 91.88. It is significantly change. Therefore, the English teaching learning process through Communicative Language Teaching (CLT) methode can enhance the students’Speaking ability. Communicative Language Teaching (CLT) methode makes the classroom situation become attractive, variative, and joyful.